FEATURES OF THE ARTISTIC HERO, IN MARIANNA GRUBER'S NOVEL "TO THE CASTLE" - Ayupov T.R (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The recent novel of an Austrian writer Marianne Gruber (1944) «Into the Castle» written in the post-modernistic style, a variation of the topic of the famous novel of Franz Kafka «The Castle», is analyzed. The paper focuses on the concepts of «a new hero» and «new readers» related to the novel key images.